2023
DOI: 10.3389/fnagi.2023.1184435
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles: a novel drug delivery system for neurodegenerative disorders

Abstract: Neurodegenerative diseases (NDs) have a slow onset and are usually detected late during disease. NDs are often difficult to cure due to the presence of the blood–brain barrier (BBB), which makes it difficult to find effective treatments and drugs, causing great stress and financial burden to families and society. Currently, small extracellular vesicles (sEVs) are the most promising drug delivery systems (DDSs) for targeted delivery of molecules to specific sites in the brain as a therapeutic vehicle due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 167 publications
(173 reference statements)
0
2
0
Order By: Relevance
“…Our data demonstrates that mTORC1 promotes endosomal transcytosis in microvascular lung endothelial cells to mediate transendothelial fatty acid delivery during metastatic outgrowth. Indeed, endothelial transcytosis involves RAB7 late endosomes, feeding into microvesicular bodies that release small extracellular vesicles, both of which contain palmitate as cargo [36][37][38] . We also demonstrated that mTORC1 regulated expression of CLSTN1, a protein implicated in endosomal trafficking and exocytosis 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrates that mTORC1 promotes endosomal transcytosis in microvascular lung endothelial cells to mediate transendothelial fatty acid delivery during metastatic outgrowth. Indeed, endothelial transcytosis involves RAB7 late endosomes, feeding into microvesicular bodies that release small extracellular vesicles, both of which contain palmitate as cargo [36][37][38] . We also demonstrated that mTORC1 regulated expression of CLSTN1, a protein implicated in endosomal trafficking and exocytosis 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rabies virus glycoprotein Open access (RVG) peptide facilitates neurospecific exosomes to target the central nervous system. 57 The αγ integrinspecific iRGD peptide aids in the delivery of doxorubicin to integrin-positive breast cancer cells in vitro and in vivo. 58 The tLyP-1 peptide, a non-small cell lung cancer (NSCLC)-homing peptide, targets neuropilin-1 (NRP1) and neuropilin-2 (NRP2) receptors, enabling the delivery of siRNA to human NSCLC cells.…”
Section: Genetic Engineeringmentioning
confidence: 99%